Pemanfaatan Limbah Tulang Sapi dan Kaca Sebagai Substitusi Parsial Semen terhadap Bata Beton Pejal - Hardinant Akesi Suratman; Hardika Putro Wijaksono; Hartono H; Shifa Fauziyah (Jurnal Sipil dan Arsitektur, 2023)
Cement is a non-renewable natural resource, this natural resource will run out over time. In this research, waste cow bone and glass were used as a partial substitute for cement for solid concrete bricks. This study used a quantitative method in the form of an experimental method referring to the General Requirements for Building Materials in Indonesia (PUBI – 1982) and the Indonesian National Standard (SNI) 03-0349-1989, with a total of 24 test objects measuring 15 x 15 x 15 cm consisting of 4 variations of composition which were tested at the age of 7 days. The content of calcium oxide (CaO) in beef bones and silica (SiO2) contained in glass can be used to increase the hardening of concrete. Based on the test results, it was found that a mixture of solid concrete bricks with 4.5% beef bone powder and 3% glass powder (BSK I), produced an optimum average compressive strength of 290.56 Kg/cm² with a water absorption value of 2.445%, declared to be entering quality I solid concrete brick. This proves that the innovation of solid concrete bricks with the addition of bovine bone and glass waste can be stated to be better than conventional solid concrete bricks, resulting in solid concrete bricks that have high compressive strength, economical price and are environmentally friendly.Keywords : solid concrete brick, glass waste, cow bone waste